Internet Use, Leisure Activities, and Memory Performance Among 65+ Residents of Baltic States - Ivleva, Viktorija; Kairys, Antanas; Jurkuvėnas, Vytautas (Socialinė teorija, empirija, politika ir praktika, 2024)
Advances in the healthcare system and socioeconomic progress have led to longer life expectancy, resulting in an ageing population and societal challenges for policymakers. Active ageing, promoted by the United Nations Economic Commission for Europe through the Active Ageing Index, highlights Capacity and Enabling Environment for Active Ageing. Information and Communication Technology (ICT) use is crucial, enabling participation in social, economic, and cultural activities (UNECE, 2020). Research indicates cognitive changes in ageing, especially memory deterioration, associating these changes with genetics, education, and professional and leisure activities (Stern, 2009). According to research, ICT positively affects cognition, enhancing memory (Almeida et al., 2012; Benge et al., 2023), but may also pose cognitive issues (Nagam, 2023). Prioritizing cognitive health among the elderly in social policies is vital, with ICT playing a key role. The present study aimed to assess the links between Internet use and memory performance after controlling for demographic factors and leisure activities. Data from the Survey of Health, Ageing, and Retirement in Europe’s 8th Wave (Börsch-Supan, 2022) included 2320 individuals aged 65–100 from Baltic countries. Memory was assessed using a modified Rey’s Auditory Verbal Learning Test. Participation in leisure activities was assessed by asking respondents if they had taken part in any of the listed activities in the past year, and Internet use was assessed by asking about Internet use in the past 7 days. Significant associations were found between memory, leisure activities, and Internet use. Internet use predicted memory capacity in older adults, remaining significant after controlling for demographics, health, and leisure activities. The current findings show that Internet use might be valuable in predicting memory functioning among older adults and can potentially contribute to the protection of cognitive function.